2020
DOI: 10.48550/arxiv.2004.01902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational neural networks

Abstract: We consider neural networks with rational activation functions. The choice of the nonlinear activation function in deep learning architectures is crucial and heavily impacts the performance of a neural network. We establish optimal bounds in terms of network complexity and prove that rational neural networks approximate smooth functions more efficiently than ReLU networks. The flexibility and smoothness of rational activation functions make them an attractive alternative to ReLU, as we demonstrate with numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…It can also be observed that the RMSE, MAE, and MAPE indicators of each variable in the PIRNN method were relatively stable in terms of both training and testing set errors. This further indicates that the PIRNN using rational activation functions exhibits extremely robust network fitting ability, which is consistent with the theoretical derivation of rational activation functions discussed in literatures [89][90][91].…”
Section: Numerical Experimentssupporting
confidence: 89%
See 1 more Smart Citation
“…It can also be observed that the RMSE, MAE, and MAPE indicators of each variable in the PIRNN method were relatively stable in terms of both training and testing set errors. This further indicates that the PIRNN using rational activation functions exhibits extremely robust network fitting ability, which is consistent with the theoretical derivation of rational activation functions discussed in literatures [89][90][91].…”
Section: Numerical Experimentssupporting
confidence: 89%
“…In the NN used in this paper, rational activation functions will be used to replace the traditional activation function, as the NN based on rational activation function have been proved to have superior approximation ability and lower training cost than the NN based on ReLU and its variants via rigorous approximation theory, a large number of theoretical deduction and practical applications [89][90][91].…”
Section: A Rational Activation Functionmentioning
confidence: 99%
“…The relative L 2 error is presented in Table 4.1 and the training process can be seen in Figure 4.1. Numerical results show that the poly-sine-Gaussian activation has the best performance in terms of the moving-average error and its best historical error is only slightly worse than the rational activation function recently proposed in [5]. We would like to remark that rational activation functions in [5] works well for regression problems but fails in our PDE problems without any meaningful solutions.…”
Section: Discontinuous Function Regressionmentioning
confidence: 87%
“…Numerical results show that the poly-sine-Gaussian activation has the best performance in terms of the moving-average error and its best historical error is only slightly worse than the rational activation function recently proposed in [5]. We would like to remark that rational activation functions in [5] works well for regression problems but fails in our PDE problems without any meaningful solutions. Hence, we only compare reproducing activation functions with rational activation functions in this example.…”
Section: Discontinuous Function Regressionmentioning
confidence: 87%
See 1 more Smart Citation